Immunogenicity, safety and clinical outcomes of the SARS-CoV-2 BNT162b2 vaccine in adolescents with type 1 diabetes - Emeksiz, Hamdi Cihan; Hepokur, Merve Nur; Şahin, Sibel Ergin; Şirvan, Banu Nursoy; Çiçek, Burçin; Önder, Aşan; Yıldız, Metin; Aksakal, Derya Karaman; Bideci, Aysun; Ovalı, Hüsnü Fahri; İşman, Ferruh (Frontiers in Pediatrics, 2023)
The mRNA-based BNT162b2 (Pfizer-BioNTech) vaccine has been shown to elicit robust systemic immune response and confer substantial protection against the severe coronavirus disease , with a favorable safety profile in adolescents. However, no data exist regarding immunogenicity, reactogenicity and clinical outcomes of COVID-19 vaccines in adolescents with type 1 diabetes (T1D). In this prospective observational cohort study, we examined the humoral immune responses and side effects induced by the BNT162b2 vaccine, as well as, the rate and symptomatology of laboratory-confirmed COVID-19 vaccine breakthrough infections after completion of dual-dose BNT162b2 vaccination in adolescents with T1D and compared their data with those of healthy control adolescents. The new data obtained after the vaccination of adolescents with T1D could guide their further COVID-19 vaccination schedule. Methods: A total of 132 adolescents with T1D and 71 controls were enrolled in the study, of whom 81 COVID-19 infection-naive adolescents with T1D (patient group) and 40 COVID-19 infectionnaive controls (control group) were eligible for the final analysis. The response of participants to the BNT162b2 vaccine was assessed by measuring their serum IgG antibodies to the spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), 4-6 weeks after the receipt of first and second vaccine doses. Data about the adverse events of the vaccine was collected after the receipt of each vaccine dose. The rate of COVID-19 vaccine breakthrough infections was evaluated in the six-month period following second vaccination. Results: After vaccinations, adolescents with T1D and controls exhibited similar, highly robust increments in anti-SARS-CoV-2 IgG titers. All the participants in the patient and control groups developed anti-SARS-CoV-2 IgG titers over 1050 AU/ml after the second vaccine dose which is associated with a neutralizing effect. None of the participants experienced severe adverse events. The rate of breakthrough infections in the patient group was similar to that in the control group. Clinical symptomatology was mild in all cases. Conclusion: Our findings suggest that two-dose BNT162b2 vaccine administered to adolescents with T1D elicits robust humoral immune response, with a favorable safety profile and can provide protection against severe SARS-CoV-2 infection similar to that in healthy adolescents.